Aripiprazole as a Candidate Treatment of COVID-19 Identified Through Genomic Analysis - Crespo-Facorro, Benedicto; Ruiz-Veguilla, Miguel; Vázquez-Bourgon, Javier; Sánchez-Hidalgo, Ana C.; Garrido-Torres, Nathalia; Cisneros, Jose M.; Prieto, Carlos; Sainz, Jesus (Frontiers in Pharmacology, 2021)
Background: Antipsychotics modulate expression of inflammatory cytokines and inducible inflammatory enzymes. Elopiprazole (a phenylpiperazine antipsychotic drug in phase 1) has been characterized as a therapeutic drug to treat SARS-CoV-2 infection in a repurposing study. We aim to investigate the potential effects of aripiprazole (an FDA approved phenylpiperazine) on COVID-19-related immunological parameters. Methods: Differential gene expression profiles of non-COVID-19 versus COVID-19 RNA-Seq samples (CRA002390 project in GSA database) and drug-naïve patients with non-affective psychosis at baseline and after three months of aripiprazole treatment were identified. An integrative transcriptomic analyses of aripiprazole effects on differentially expressed genes in COVID-19 patients was performed. Findings: 82 out the 377 genes (21.7%) with expression significantly altered by aripiprazole have also their expression altered in COVID-19 patients and in 93.9% of these genes their expression is reverted by aripiprazole. The number of common genes with expression altered in both analyses is significantly higher than expected (Fisher's Exact Test, two tail; P value=3.2e-11). 11 KEGG pathways were significantly enriched with genes with altered expression both in COVID-19 patients and aripiprazole medicated non-affective psychosis patients (P adj<0.05). The most significant pathways were associated to immune responses and mechanisms of hyperinflammation-driven pathology (i.e.,"inflammatory bowel disease (IBD)" (the most significant pathway with a P adj of 0.00021), "Th1 and Th2 cell differentiation" and "B cell receptor signaling pathway") that have been also associated with COVID19 clinical outcome. Interpretation: This exploratory investigation may provide further support to the notion that a protective effect is exerted by aripiprazole (phenylpiperazine) by modulating the expression of genes that have shown to be altered in COVID-19 patients. Along with many ongoing studies and clinical trials, repurposing available medications could be of use in countering SARS-CoV-2 infection, but require further studies and trials.